Large Scale Composite Nanowires and 3D Nanostructures for Energy Conversion and Storage - Kiong, Ling Jin; Hassanien, Bakr Zinab; Bhupender, Pal; Lathakumary, Vijayan Bincy; Shengyuan, Yang; M. M., Yusoff; Rajan, Jose (Beijing Institute of Technology, 2018)
Composites of functional materials have long been synthesized for achieving enhanced physical and chemical properties such that they serve improved functions for a range of nanoelectronic devices and architectures. This is because many nanoelectronic devices demands materials of multiple functions including high conductivity and high surface area. In particular, these two functions are mutually competing in nanostructured materials – when the surface area increases as a result of nanostructuring processes, the increased surface fraction imposes surface states that lie within the bandgap of the material and subsequently the electrical conductivity is lowered. Many attempts have been adopted in the past to have high surface area and highly conducting materials in the single material system; however, making a composite is the most simple one and could be industrially accepted. Composite properties are achieved through many methods such as physical mixing of its components, chemical methods such as core/shell, hierarchical structures, nanoparticle-decorated nanowires, and carbon-reinforced porous materials are few examples. However, preparing a composite in the form of a nanowire or a 3D nanoflower is relatively new. Given the paramount importance of energy, recently energy conversion and storage devices are researched globally with high intensity. Optical transparency and workability at low light conditions enable the dye-sensitized solar cells (DSSCs) and the perovskite solar cells (PSCs) as desirable choice as smart windows in modern buildings for adding aesthetics with diverse choice of colors while producing clean electricity so as to realize zero-energy buildings. In both of these solar cells, the photoactive material is chemically developed from solutions on a wide bandgap material, known as photoelectrode. The photoelectrode influence the performance of the solar cells in many ways as they are either the charge separation medium or the charge transport medium or both. Commercially available mesoporous TiO2 has been a widely investigated material; but the sluggish charge kinetics due to the surface charges and intrinsic poor electrical conductivity triggered an intensive search on new materials worldwide. As a result many materials and materials architectures are developed with superior properties than the commercial choice; however, most of new materials are hardly scalable to the industrial levels. Among them, nanowires and 3D nanostructures such as flowers offer many advantages such as anisotropic charge dynamics, large surface area, and high crystallinity. Again, most of the materials synthesized thereby are through hardly scalable chemical processes. Similarly, storage of electrical energy in media and protocols with high energy and power densities have received a revived interest due to high power mobile electrical devices, electric vehicles, and other disconnected from grid but electrically powered technologies such as drones and robots. As a result, many new battery concepts such as sodium batteries, lithium-air, and lithium-Sulphur are currently under intensive research as a replacement for traditional lithium ion batteries. One of the promising replacement for batteries is battery-supercapacitor hybrids (BSHs) owing to its potentially higher power density (<5 kW kg-1) and longer life cycle (>100,000) compared to that of batteries; however, their energy density is rather unimpressive because of the sluggish charge kinetics of the electrode materials used. Therefore, making a composite with a highly conductive material with a highly electrochemically active material is a potential remedy. In the course of our research on the development of materials for energy conversion and storage, we have developed a range of composite materials in large quantities as nanobelts, nanowires and 3D nanoflowers through multineedle electrospinning techniques. The resulting materials performed synergistically and the energy conversion and storage devices fabricated using them gave superior properties than those fabricated using their constituents.